2013
DOI: 10.3126/jonmc.v2i1.7669
|View full text |Cite
|
Sign up to set email alerts
|

A Pattern Of Ocular Morbidity In Patients Attending Anophtalmic Clinic In A Rural Part Of Western Nepal

Abstract: Background/ Aim: Very few reports exist regarding the causes of ocular morbidity in western Nepal. The study is performed to identify the causes of ocular morbidity in a clinic at Waling in western Nepal. Method: A retrospective study of all patients attending the eye clinic at Waling from August 2010 to August 2011 was done. Result: The study included 915 patients, 617 (67.5%) females, and 298 (32.5 %) males. Refractive error was the most common ocular morbidity accounting 26.8% followed by conjunctivitis 20.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 7 publications
2
7
0
Order By: Relevance
“…Age distribution of the community outreach clients, the age 0 -10 years (18.2%) were the most active participant. ratio of 2.5:1, these findings are similar to other studies in Nigeria and Nepal [5] [7]. Elsewhere, a study reported male preponderance and another showed equal accessibility of both gender [10] [11].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Age distribution of the community outreach clients, the age 0 -10 years (18.2%) were the most active participant. ratio of 2.5:1, these findings are similar to other studies in Nigeria and Nepal [5] [7]. Elsewhere, a study reported male preponderance and another showed equal accessibility of both gender [10] [11].…”
Section: Discussionsupporting
confidence: 89%
“…These findings are similar to a study conducted in Ethiopia, the most common of which was conjunctivitis, but the percentage was much lower (29%), [6]. A similar study in West Nepal showed that refractive errors (26.8%) were the most common ocular morbidity followed by conjunctivitis (20.6%) [5]. Glaucoma was seen in 4 (0.5%) participants classified as one of the least common causes of morbidity, contrary to findings in studies that showed that it was among the most prevalent ocular morbidities in and the most important cause of blindness in Nigeria [14] [15].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The observations made in this study were similar to our study with same pattern of eye diseases encountered. Another study conducted in Nepal 21 Incidence of cataract was negligible in our study as compared with other studies since we had active military soldiers as study population which were mostly in pre-senile age group but presbyopia was a common complaint. Our study has inherent limitation of lesser Number of subjects but this was due to the study population being limited to United Nations peace keeping soldiers.…”
Section: Discussionmentioning
confidence: 50%
“…In the same vein, Agyemang-Mireku in Ghana found the commonest eye disorders seen to be conjunctivitis (39.70%), cataract (24.40%), glaucoma (9.70%) and refractive error (8.90%) [9]. In western Nepal, refractive error was the most common ocular morbidity accounting for 26.8% of cases; followed by conjunctivitis (20.6%), cataract (11.8%), pterygium (6%), chalazion/stye (4%), ectropion/entropion (3.9%), keratitis (3.8%), dry eyes syndrome (2.8%), and corneal opacities (2.3%) [10]. Similarly, a retrospective study in India showed that conjunctivitis was the commonest ocular disorder at 21.94%; others were cataract -9.2%, refractive error -15.2%, dacryocystitis -6.51% and blepharitis -3.2% [11].…”
Section: Introductionmentioning
confidence: 99%